Adsorption of trans‐ and cis‐Resveratrol on Graphene. Issue 2 (1st October 2018) - Domokos, Réka‐Anita; Potara, Monica; Aştilean, Simion; Chiş, Vasile
Abstract : Resveratrol has a strong antioxidant activity which renders this compound very interesting for the biomedical field. However, the low aqueous solubility is a limiting factor for its bioavailability. For practical applications as a drug or nutraceutical, resveratrol needs to be transported by nanocarriers like, for instance, graphene materials. In this work, we explore the possibility of adsorbing the resveratrol isomers on graphene materials and the possible discrimination of enantiomers by such surfaces. The interaction between the resveratrol's ( trans ‐ and cis ‐) isomers and graphene oxide are investigated by using UV‐Vis spectroscopy and zeta potential measurements. Quantum chemical calculations based on density functional theory are used to get insights into the geometries of adsorption and interaction energies between resveratrol and graphene. Abstract : The interaction between resveratrol isomers and graphene oxide is investigated by using UV–Vis spectroscopy and zeta potential measurements. Density functional theory calculations are used to get insights into the geometries of adsorption and interaction energies between resveratrol and graphene. The results provided by this study would help to develop nanocarriers of resveratrol for various biomedical applications.